2016
DOI: 10.1242/jeb.132431
|View full text |Cite
|
Sign up to set email alerts
|

Altitude matters: differences in cardiovascular and respiratory responses to hypoxia in bar-headed geese reared at high and low altitudes

Abstract: Bar-headed geese (Anser indicus) fly at high altitudes during their migration across the Himalayas and Tibetan plateau. However, we know relatively little about whether rearing at high altitude (i.e. phenotypic plasticity) facilitates this impressive feat because most of what is known about their physiology comes from studies performed at sea level. To provide this information, a comprehensive analysis of metabolic, cardiovascular and ventilatory responses to progressive decreases in the equivalent fractional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 48 publications
1
57
0
Order By: Relevance
“…Despite this, high-altitude avian species such as the bar-headed goose (Anser indicus) and Andean goose (Chloephaga melanoptera) have been shown to preferentially increase V t over f R (Scott and Milsom, 2007;Lague et al, 2016; S.L.L., B.A.C., L.A., Y. Zhong, A. P. Farrell, K.G.M., Y. Wang and W.K.M., unpublished data). We wondered whether this deeper, slower breathing pattern might be found in other high-altitude species, and whether the mechanical design of the respiratory systems of high-altitude species might be altered to reduce the metabolic cost of potentially employing this higher tidal volume strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, high-altitude avian species such as the bar-headed goose (Anser indicus) and Andean goose (Chloephaga melanoptera) have been shown to preferentially increase V t over f R (Scott and Milsom, 2007;Lague et al, 2016; S.L.L., B.A.C., L.A., Y. Zhong, A. P. Farrell, K.G.M., Y. Wang and W.K.M., unpublished data). We wondered whether this deeper, slower breathing pattern might be found in other high-altitude species, and whether the mechanical design of the respiratory systems of high-altitude species might be altered to reduce the metabolic cost of potentially employing this higher tidal volume strategy.…”
Section: Introductionmentioning
confidence: 99%
“…High-altitude deer mice appear much like Tibetan humans, plateau pika and bar-headed geese, which breathe as much or more than hypoxia-acclimated lowlanders. [16][17][18][19][20][21] This strategy contrasts the blunted HVR of Andean humans, guinea-pigs and Andean geese. [22][23][24] These differences have previously been suggested to reflect divergent evolutionary outcomes arising from tradeoffs between O 2 uptake vs. CO 2 /pH homeostasis and the metabolic costs of breathing.…”
Section: Figurementioning
confidence: 99%
“…12,14,15 In some high-altitude populations or species, including Tibetan humans, plateau pika (Ochotona curzoniae), and bar-headed geese (Anser indicus), total and/or alveolar ventilation is similar or enhanced compared to lowlanders. [16][17][18][19][20][21] In contrast, some other highland taxa exhibit a blunted HVR, including Andean humans, guinea-pigs (Cavia porcellus) and Andean geese (Chloephaga melanoptera). [22][23][24] With some exceptions, 24 the underlying mechanisms of these evolved changes in the control of breathing are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…However, most studies investigating the physiology of migration have been conducted at low altitude and have largely ignored this transient but potentially important altitude component. Outside of a few species adapted to high altitude (Barve et al, 2016;Fedde et al, 1989;Lague et al, 2016;Scott and Dawson, 2017;Scott et al, 2015), physiological responses to exercise at high altitude in many passerines are still poorly understood. Borras et al (2010) found that citril finches (Carduelis citronella) increased Hct in response to increases in altitude, but these birds were transported passively to high elevation by the researchers.…”
Section: Introductionmentioning
confidence: 99%